Análisis teórico del efecto del cloruro de potasio sobre el movimiento de bordes de grano hielo - Di Prinzio, Carlos Leonardo (2008)
The migration theory for doped grain boundary, developed by J. W. Cahn, was modified to describe the experimental grain boundary migration results in potassium chloride (ClK) doped ice samples. The ClK concentration in the analyzed ice samples were 1 y 10 mol/l and the temperatures range was between -5°C and -20°C. The model describes satisfactory the decrease of the grain boundary mobility with the impurity concentration and the increase of the activation energy associated to the doped grain boundary migration. The grain boundary mobilities agree with the experimental values if the grain boundary thickness is considered m8102forCTo15 and m10105for below temperatures